Konsep Hukum Biodiversitas dalam Dunia Digital (Fondasi Teoritik Pengembangan Hukum Lingkungan Indonesia Berbasis Biodiversitas) - Efridani Lubis (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2021)
Biodiversity protection in Indonesia becomes an urge considering that the number of it is numerous since Indonesia categorized as one mega-biodiversity countries in the world. Biodiversity protection in Indonesia is still based on international system which is political approach. While biodiversity conservation needs all aspects to support the conservation. One of the proposal in the term of the conservation is introducing Biodiversity Law as part of education system for legal profession. Developing existing Environment Law lead to the possibility of Biodiversity Law since the two subject has similar system. The difference is Biodiversity Law focus on protection and utilization of biodiversity in general term including genetic resources as a clear and structured protection instrument so that explore and exploit the biodiversity could be done with full responsibility for assurance to next generation beneficial. However, this will take several steps, and the first step is inserting the subject to Environment Law as material course for law students in Indonesia.